(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Background: Spinal tumor is one of the causes of back pain, sensory motor deficit and bowel bladder dysfunction. Evaluation of postoperative mortality, morbidity and outcomes after resection of spinal cord tumors is critical to the practice of evidencebased medicine. Hence, it is important to carefully examine surgical outcomes at an institutional level. Objectives: The aim of the study was to describe the results of benign spinal tumor after surgical treatment according to location. Materials & Method: This quasi-experimental study was conducted in the Department of Neurosurgery, Chittagong Medical College and Hospital for a period of 12 months. Twenty eight cases of benign spinal tumor underwent surgical treatment were enrolled in the study. Average hospital stay from surgery to discharge was 12-15 days. Postoperative neurological outcome in Frankel’s grade and bowel bladder involvement were assessed from 1st POD to 3rd month after surgery and data were recorded at 7th POD, 1st month and 3rd month after surgery. Collected data were analyzed by using SPSS-23. Results: Among the 28 cases, 15 were men and 13 were women. The mean age was 36.19 (±14.29) years and age range was 15 to 62 years. Twenty three (82.14%) patients improved by at least one Frankel grade and remaining five (17.86%) patients maintained their preoperative Frankel grade. Out of eight (28.6%) cases with absent bowel bladder dysfunction before surgery six (75%) recovered within three months. Postoperative deterioration was not observed in any of the included case. Ten (35.7%) patients had excellent outcome (having Frankel grade E with normal bowel bladder control) and 18 patients (64.3%) had good/fair outcome (partial recovery or clinically insignificant recovery) after 3 months. Age, gender and location (axial and sagittal) of benign spinal tumor were not found to have significant variation of neurological outcome. Conclusion: Majority of patients irrespective of the location (axial/sagittal) of the tumor had a favorable clinical outcome three months after the operation. Bang. J Neurosurgery 2024; 13(2): 130-139